ЕПІСТЕМОЛОГІЧНІ ЗАСАДИ ВИВЧЕННЯ ЗНАННЯ ЯК СУБ'ЄКТИВНОГО УТВОРЕННЯ (Педагогіка вищої та середньої школи, 2008)
The article concerns the epistemological study of knowledge as the subjective unity viewed by native and abroad investigations. The epistemology as a branch of as well as the manifestation of subjective form of knowledge and knowing are under discussion. Main directions of the abroad epistemological studies are analyzed.